Second Chance. - Johnston, Caitlin (American Journalism Review)
The article discusses the relation between newspapers and tablet computers, particularly Apple Inc.'s iPad tablet computer, in light of the attitudes of newspaper publishers toward the Internet. Topics include the high median incomes of tablet computer users, the need for newspapers to modify content for tablet computers, and the layout of content accessed using tablet computers. Also noted are research on tablet computer user habits, the potential for a payment model for newspaper content on tablet computers, and the use of the web protocol HTML 5 by the newspapers "Financial Times" and "Boston Globe."